Prevalence, Years Lived With Disability, and Time Trends for 16 Causes of Blindness and Vision Impairment: Findings Highlight Retinopathy of Prematurity - Zhang, Rui-Heng; Liu, Yue-Ming; Dong, Li; Li, He-Yan; Li, Yi-Fan; Zhou, Wen-Da; Wu, Hao-Tian; Wang, Ya-Xing; Wei, Wen-Bin (Frontiers in Pediatrics, 2022)
Background: Cause-specific prevalence data of vision loss and blindness is fundamental for making public health policies and is essential for prioritizing scientific advances and industry research. Methods: Cause-specific vision loss data from the Global Health Data Exchange was used. The burden of vision loss was measured by prevalence and years lived with disability (YLDs). Findings: In 2019, uncorrected refractory error and cataract were the most common causes for vision loss and blindness globally. Women have higher rates of cataract, age-related macular degeneration (AMD), and diabetic retinopathy (DR) than men. In the past 30 years, the prevalence of moderate/severe vision loss and blindness due to neonatal disorders has increased by 13.73% and 33.53%, respectively. Retinopathy of prematurity (ROP) is the major cause of neonatal disorders related vision loss. In 2019, ROP caused 101.6 thousand (95% uncertainty intervals [UI] 77.5-128.2) cases of vision impairment, including 49.1 thousand (95%UI 28.1-75.1) moderate vision loss, 27.5 thousand (95%UI 19.3-36.60) severe vision loss and, 25.0 thousand (95%UI 14.6-35.8) blindness. The prevalence of new-onset ROP in Africa and East Asia was significantly higher than other regions. Variation of preterm birth prevalence can explain 49.8% geometry variation of ROP-related vision loss burden among 204 countries and territories. After adjusting for preterm prevalence, government health spending per total health spending (%), rather than total health spending per person, was associated with a reduced burden of ROP-related vision loss in 2019 (-0.19 YLDs for 10% increment). By 2050, prevalence of moderate, severe vision loss and blindness due to ROP is expected to reach 43.6 [95% UI 35.1-52.0], 23.2 [95% UI 19.4-27.1], 31.9 [95% UI 29.7-34.1] per 100,000 population. Conclusion: The global burden of vision loss and blindness highlights the prevalent of ROP, a major and avoidable cause for childhood vision loss. Advanced screening techniques and treatments have shown to be effective in preventing ROP-related vision loss and are urgently needed in regions with high ROP-related blindness rates, including Africa and East Asia.